2002
DOI: 10.1017/s0021859602002101
|View full text |Cite
|
Sign up to set email alerts
|

Responses of tomato plants associated with the arbuscular mycorrhizal fungus Glomus clarum during drought and recovery

Abstract: Mycorrhizal and non-mycorrhizal tomato plants (Lycopersicon esculentum Mill. cv ‘Amalia’) were subjected to water stress by withholding irrigation water for 72 hours and then reirrigated for 120 hours. Water stress reduced root mycorrhizal colonization, although the presence of the fungus Glomus clarum stimulated tomato plant growth. During the stress period the effect on the growth was more pronounced in aerial biomass than in the root biomass. The decrease in the soil water potential generated a decrease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 0 publications
3
33
1
Order By: Relevance
“…The lower values of L in AM plants than in nonAM plants disagree with previous reports that have showed enhanced L in droughted tomato, rosemary and lettuce AM plants as compared to nonAM plants (Dell'amico et al 2002;Sánchez-Blanco et al 2004;Aroca et al 2008b). Nevertheless, Augé (2001) reported that root hydraulic conductivity is generally not improved by the AM symbiosis in the absence of AM-induced growth or P effects, as we found for plant growth in this study.…”
Section: Root Hydraulic Properties and Pip Aquaporin Gene Expression contrasting
confidence: 99%
“…The lower values of L in AM plants than in nonAM plants disagree with previous reports that have showed enhanced L in droughted tomato, rosemary and lettuce AM plants as compared to nonAM plants (Dell'amico et al 2002;Sánchez-Blanco et al 2004;Aroca et al 2008b). Nevertheless, Augé (2001) reported that root hydraulic conductivity is generally not improved by the AM symbiosis in the absence of AM-induced growth or P effects, as we found for plant growth in this study.…”
Section: Root Hydraulic Properties and Pip Aquaporin Gene Expression contrasting
confidence: 99%
“…Previous work also studied the relationship between tomato and AM fungi under WS (Dell'Amico et al, 2002;Subramanian et al, 2006;Aroca et al, 2008;Wang et al, 2014;Ruiz-Lozano et al, 2016). The discrepancy among data already available could be due to the use of different plant varieties and fungal species/isolates as well as to different growth and drought stress conditions (Augé et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Processing tomato is one of the most economically important and widespread horticultural crops in the world [6,7], and in 2018, its production was~34 million tons [8]. In addition, processing tomato is extremely dependent on irrigation water, the average water requirement ranging from~400 to 600 mm during the growing season based on the climatic conditions of the area [9].…”
Section: Introductionmentioning
confidence: 99%
“…AM fungi are ubiquitous in soil and establish symbiotic relationships with the roots of many cultivated plants [6,16,17]. Plant-AM fungi interaction is mutualistic as the fungi can help plants overcome abiotic and biotic stresses and improve mineral nutrient and water uptake while the host plant provides photosynthates [16] and lipids [18].…”
Section: Introductionmentioning
confidence: 99%